Using Minecraft to cultivate student interest in STEM - Tablatin, Christine Lourrine S.; Casano, Jonathan D. L.; Rodrigo, Maria Mercedes T. (Frontiers in Education, 2023)
Due to the popularity and flexibility of Minecraft, educators have used this game to develop instructional materials and activities to cultivate student interests in science, technology, engineering and mathematics (STEM). One example of such an initiative is the What-If Hypothetical Implementations in Minecraft (WHIMC) project of the University of Illinois Urbana Champaign. The study reported in this paper describes a WHIMC deployment in the Philippines and the effects this deployment had on student STEM interest. The study used quantitative and qualitative methods to determine the effect of WHIMC on the STEM interest of Filipino students. We performed quantitative analysis of the pre- and post-STEM Interest Questionnaire (SIQ) ratings and Game Experience Questionnaire (GEQ) ratings of the high- and low-performers to determine the effect of using WHIMC in the students’ STEM interest and the difference between the game experience of high- and low-performers, respectively. Qualitative analysis of the answers to the open-ended questions about the attributes of the module was also conducted to determine the relationship between the module attributes and student performance. The analysis of the aggregated SIQ ratings before and after using the WHIMC-based modules revealed only a minimal effect on the STEM interests of the students. However, there was a significant effect in the Choice Actions construct, which implies that students recognize the importance of studying hard if they want to pursue STEM-related careers. Further, the analysis of the overall GEQ of high-performers and low-performers also revealed no significant difference. Although no significant difference was observed in the overall GEQ, high-performers had significantly higher GEQ ratings in the Immersion dimension. This result suggested that high-performers had a more positive, engaging, and enjoyable learning experience. Moreover, the findings on the favorite module attributes suggested that students perform better in the out-of-game assessments when they like all the module attributes. This implies that students must be engaged in the game and learning task aside from being interested in the learning topic to have better assessment scores. The study also showed that open-ended learning environments coupled with tasks that demand exploration, observation, and higher-ordered thinking are demanding even on high-performers.